Live Monitoring System for Recognizing Varied Emotions of Autistic Children - Fadhil, Tamara Z.; Mandeel, Ali R. (2018 International Conference on Advanced Science and Engineering (ICOASE), 2018)
A rising line of research that endeavors to uncover implicit mechanisms of Autism Spectrum Disorder (ASD). Children with ASD can't express their feelings unequivocally; this makes it troublesome for the parents and overseers related with these youngsters to comprehend their conductance, Causing a noteworthy difficulty in the child's initial formative stages. In this paper, a system was implemented to monitor children with autism remotely to help specialists follow their patients' progress and analyzing the collecting data. The system consists of NodeMCU ESP8266, galvanic skin response (GSR) sensor, broker (server) and a smartphone or personal computer. NodeMCU (ESP8266) reads the data from the GSR sensor and publishes it on the server. This system observes the subjects' reactions to different emotions like sadness, happiness, nervous, hunger, relaxation and trepidation, and then records the data. Message Queuing Telemetry Transport (MQTT) protocol had been used to publish the data online. Finally, a comparison had been made between the obtained data for children with autism and without autism.